A Study of clinical profile, disease severity and treatment response of Movement disorders at a tertiary care teaching hospital - Shaik Afsar Pasha; Phanibhushan Phanibhushan; T. V. Pavan Kumar; B. Bhaskara Rao; Shaik Arif Pasha (International Journal of Medical Research and Review, 2018)
Background: Movement disorders are one of the common neurological problems seen by General physicians and neurophysicians. The clinical phenotype of Movement disorders is variable.Aim of the study: The objective of the study was to study the clinical profile, disease severity and treatment response of Movement disorders at a tertiary care teaching hospital.Results: The present study was a prospective observational study comprising 55 clinically detectable patients of movement disorders. Out of fifty-five, the frequency of various Movement disorders were as follows: Parkinson’s disease- 25 (45.5%), Wilson`s disease (WD)-9 (16.36%), Progressivesupranuclear palsy- 8(14.54%), Essential Tremor with Parkinson disease 5 (9.0%), Choreiform disorders- 5(9.0%). Mean MDS-UPDRS Part III score in OFF stage of PD was 57.7±13.2 and in ON stage was 28.2±10.2 suggesting significant improvement. Seventy-six percentages of PD patients had Good response to Dopaminergic agonists and Levodopa administration, while better response was seen in WD, ET+PD and the poor response in PSP patients respectively.Conclusion: Identifying and describing the clinical phenomenology of Movement disorders is the first step in the diagnostic evaluation of the patients as against to the localization in General Neurological disorders. Disease severity scales do assess the progression of the disease at the earliest and there are affordable regimes of various medications are available to treat them at the earliest, so as to reduce the morbidity and to increase health related quality of life.